Thermoplastic resin composition, method for preparing the same, and molded article comprising the same

By developing a thermoplastic resin composition with a specific composition, the problem of existing thermoplastic resins releasing toxic gases during combustion and whitening when bending is solved, achieving excellent processability, mechanical properties and heat resistance while avoiding whitening phenomenon .

CN115397914BActive Publication Date: 2025-02-14LG CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180019785.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-01-22
Filing Date
2021-12-07
Publication Date
2025-02-14
Estimated Expiration
2041-12-07

AI Technical Summary

Technical Problem

Existing thermoplastic resins such as PVC resin and t-PMMA resin release toxic gases during combustion and are prone to whitening during bending, affecting appearance and aesthetics.

Method used

A thermoplastic resin composition has been developed, which comprises 25-75% graft copolymer of alkyl acrylate rubber, 18-47% aromatic vinyl compound-vinyl having a weight average molecular weight of 70,000-150,000 The cyanide compound copolymer and 3-28% of the same copolymer with a weight average molecular weight greater than 150,000 can ensure that the composition has excellent processability and mechanical properties during calendering and T-die extrusion. And prevent whitening.

Benefits of technology

The thermoplastic resin composition does not contain harmful phthalate compounds, does not release toxic gases during fire, has equal or better processability as PVC resin, excellent mechanical properties, surface hardness and heat resistance, and No albinism occurs during bending.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115397914B_ABST
    Figure CN115397914B_ABST
Patent Text Reader

Abstract

The present invention relates to a thermoplastic resin composition, a method for preparing the same, and a molded article comprising the same. More specifically, the present invention relates to a thermoplastic resin composition, wherein the alkyl acrylate coverage value (X) of the thermoplastic resin composition calculated by equation 1 is 67% or more, and the present invention also relates to a method for preparing the thermoplastic resin composition and a molded article comprising the thermoplastic resin composition. The thermoplastic resin composition according to the present invention does not contain phthalate compounds that are environmental hormones harmful to the human body; does not release toxic gases in the event of a fire; has processability equal to or better than that of PVC resin used as a material for calendering and T-die extrusion; has excellent mechanical properties such as impact strength, tensile strength and elongation, surface hardness and heat resistance; and can prevent whitening during bending due to excellent non-whitening properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the priority of Korean Patent Application No. 10-2021-0009291 filed in the Korean Intellectual Property Office on January 22, 2021, the disclosure of which is incorporated herein by reference.

[0003] The present invention relates to a thermoplastic resin composition, a method for preparing the same, and a molded article comprising the same. More specifically, the present invention relates to a thermoplastic resin composition, a method for preparing the same, and a molded article comprising the same, wherein the thermoplastic resin composition does not contain phthalate compounds that are environmental hormones harmful to the human body; does not release toxic gases in the event of a fire; has processability equal to or better than that of conventional PVC resins used as materials for calendaring and T-die extrusion; has excellent mechanical properties such as impact strength, tensile strength, and elongation, surface hardness, and heat resistance; and can prevent whitening during bending due to excellent non-whitening properties. Background Art

[0004] Polyvinyl chloride (hereinafter referred to as "PVC") resin and t-polymethyl methacrylate (hereinafter referred to as "t-PMMA") resin are mainly used for manufacturing decorative panels through T-die extrusion processing and calendering.

[0005] PVC resin is a homopolymer of vinyl chloride and a copolymer containing more than 50% by weight of vinyl chloride. It is one of the five general thermoplastic resins prepared by suspension polymerization or emulsion polymerization. When polyvinyl chloride resin is prepared by suspension polymerization, plasticizers, stabilizers, fillers, pigments and auxiliary materials with special functions are added. The polyvinyl chloride resin prepared in this way is used to manufacture various products such as films, sheets, wires and pipes through various processing methods. However, since PVC resin produces chlorine and hydrogen chloride gas during combustion, harmful gases will be produced in the event of a fire. In addition, phthalate compounds are used as plasticizers to give PVC resin flexibility. Phthalate compounds are known as environmental hormones that are harmful to the human body.

[0006] In addition, t-PMMA resin is a resin developed to improve the low brittleness of PMMA resin, and is prepared by mixing a polymer obtained by polymerizing acrylic rubber as a core and methyl methacrylate as a shell with a polymethyl methacrylate resin. t-PMMA resin has excellent surface hardness and colorability, but its use is limited due to its low impact strength at room temperature and low temperature.

[0007] In order to solve these problems, research on materials that can replace PVC resin and t-PMMA resin is being actively carried out. Among them, acrylonitrile-styrene-acrylate resin (hereinafter referred to as "ASA resin") has excellent weather resistance, light resistance, coloring, chemical resistance and impact resistance, and is therefore used in various fields such as automobiles, building materials and sundries. In particular, compared with PVC resin, ASA resin has excellent processing stability and does not contain heavy metal components, so ASA resin has attracted much attention as an environmentally friendly material.

[0008] In addition, as the importance of aesthetics in the market increases, research is being conducted to achieve luxurious appearance and excellent colorability and weather resistance by finishing the surface of a substrate such as acrylonitrile-butadiene-styrene resin, PVC resin, or an iron plate with ASA resin. These decorative materials are mainly manufactured in the form of a film. The decorative material is made into a final product through a bending process such as bending or folding according to the shape of the substrate. However, due to the characteristics of thermoplastic ASA resin, when the above-mentioned finishing treatment is applied at room temperature, whitening occurs at the folded portion, resulting in loss of original color and deterioration of appearance and aesthetics.

[0009] Therefore, there is a need to develop a thermoplastic resin composition that is suitable for various processes such as T-die extrusion processing and calendaring processing, is environmentally friendly, and does not cause whitening after bending processing.

[0010] [Prior art literature]

[0011] [Patent Document]

[0012] Japanese Patent No. 1995-033470 Summary of the invention

[0013] Technical issues

[0014] Therefore, the present invention has been accomplished in view of the above problems, and an object of the present invention is to provide a thermoplastic resin composition which does not contain phthalate compounds which are environmental hormones harmful to the human body; does not release toxic gases in the event of a fire; has processability equal to or better than that of PVC resin during calendering and T-die extrusion; has excellent mechanical properties such as impact strength, tensile strength and elongation, surface hardness and heat resistance; and can prevent whitening during bending due to excellent non-whitening property.

[0015] Another object of the present invention is to provide a method for preparing the thermoplastic resin composition.

[0016] Another object of the present invention is to provide a molded article produced using the thermoplastic resin composition.

[0017] The above and other objects can be achieved by the present invention described below.

[0018] Technical Solution

[0019] According to one aspect of the present invention, there is provided a thermoplastic resin composition comprising: 25 wt % to 75 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer (A) containing an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm; 18 wt % to 47 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (B) having a weight average molecular weight of 70,000 g / mol to 150,000 g / mol; and 3 wt % to 28 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (C) having a weight average molecular weight greater than 150,000 g / mol and less than or equal to 250,000 g / mol, wherein the thermoplastic resin composition has an alkyl acrylate coverage value (X) of 67% or more as calculated by the following equation 1:

[0020] [Equation 1]

[0021] X = {(GY) / Y} × 100,

[0022] Herein, G represents the gel content (weight %) based on the total weight of the thermoplastic resin composition, and Y represents the content (weight %) of the alkyl acrylate in the gel based on the total weight of the thermoplastic resin composition.

[0023] In addition, the present invention can provide a thermoplastic resin composition, comprising: 25 wt % to 75 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer (A) containing an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm; 18 wt % to 47 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (B) having a weight average molecular weight of 70,000 g / mol to 150,000 g / mol; and 3 wt % to 28 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (C) having a weight average molecular weight greater than 150,000 g / mol and less than or equal to 250,000 g / mol, wherein the thermoplastic resin composition has a heat deformation temperature of 71° C. or above when measured under a load of 18.6 kgf according to ASTM D648.

[0024] In addition, the present invention can provide a thermoplastic resin composition, which comprises: 25% to 75% by weight of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer (A) containing an alkyl acrylate rubber having an average particle size of 50nm to 120nm; 18% to 47% by weight of an aromatic vinyl compound-vinyl cyanide compound copolymer (B) having a weight average molecular weight of 70,000 g / mol to 150,000 g / mol; and 3% to 28% by weight of an aromatic vinyl compound-vinyl cyanide compound copolymer (C) having a weight average molecular weight greater than 150,000 g / mol and less than or equal to 250,000 g / mol, wherein the graft copolymer (A) comprises 20% to 60% by weight of an alkyl acrylate and 40% to 80% by weight of an aromatic vinyl compound-vinyl cyanide compound copolymer.

[0025] According to another aspect of the present invention, there is provided a method for preparing a thermoplastic resin composition, the method comprising mixing and extruding 25 wt % to 75 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer (A) containing an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm, 18 wt % to 47 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (B) having a weight average molecular weight of 70,000 g / mol to 150,000 g / mol, and 3 wt % to 28 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (C) having a weight average molecular weight greater than 150,000 g / mol and less than or equal to 250,000 g / mol at 200° C. to 300° C. and 100 rpm to 500 rpm, wherein the thermoplastic resin composition has an alkyl acrylate coverage value (X) calculated by the following equation 1 of 67% or more:

[0026] [Equation 1]

[0027] X = {(GY) / Y} × 100,

[0028] Herein, G represents the gel content (weight %) based on the total weight of the thermoplastic resin composition, and Y represents the content (weight %) of the alkyl acrylate in the gel based on the total weight of the thermoplastic resin composition.

[0029] In addition, the present invention can provide a method for preparing a thermoplastic resin composition, which comprises mixing and extruding 25 wt % to 75 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer (A) containing an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm, 18 wt % to 47 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (B) having a weight average molecular weight of 70,000 g / mol to 150,000 g / mol, and 3 wt % to 28 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (C) having a weight average molecular weight greater than 150,000 g / mol and less than or equal to 250,000 g / mol at 200° C. to 300° C. and 100 rpm to 500 rpm, wherein the thermoplastic resin composition has a heat deformation temperature of 71° C. or higher when measured under a load of 18.6 kgf according to ASTM D648.

[0030] In addition, the present invention can provide a method for preparing a thermoplastic resin composition, which comprises mixing and extruding 25 wt % to 75 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer (A) containing an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm, 18 wt % to 47 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (B) having a weight average molecular weight of 70,000 g / mol to 150,000 g / mol, and 3 wt % to 28 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (C) having a weight average molecular weight greater than 150,000 g / mol and less than or equal to 250,000 g / mol at 200° C. to 300° C. and 100 rpm to 500 rpm, wherein the graft copolymer (A) contains 20 wt % to 60 wt % of an alkyl acrylate and 40 wt % to 80 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer.

[0031] According to another aspect of the present invention, a molded article comprising the thermoplastic resin composition is provided.

[0032] Beneficial Effects

[0033] According to the present invention, the present invention has the following effects: providing a thermoplastic resin composition, a method for preparing the thermoplastic resin composition, and a molded article comprising the thermoplastic resin composition, wherein the thermoplastic resin composition does not contain phthalate compounds that are environmental hormones harmful to the human body; does not release toxic gas in the event of a fire; has processability equal to or better than that of PVC resin as a material for calendaring and T-die extrusion; has excellent mechanical properties such as impact strength, tensile strength and elongation, surface hardness and heat resistance; and can prevent whitening during bending due to excellent non-whitening property. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Included are images of films produced in Example 2 (left figure) and Comparative Example 1 (right figure) photographed after being hit using a Gardner impact tester to check whether whitening occurs. DETAILED DESCRIPTION

[0035] Hereinafter, the thermoplastic resin composition of the present invention, a method for preparing the same, and a molded article including the same will be described in detail.

[0036] The present inventors have confirmed that when an alkyl acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer containing a rubber having a predetermined average particle size and two or more aromatic vinyl compound-vinyl cyanide compound copolymers having different weight average molecular weights are mixed at a predetermined composition ratio, and the alkyl acrylate coverage value of the thermoplastic resin composition is adjusted within a predetermined range, the thermoplastic resin composition has processability equal to or better than that of PVC resin during calendering and T-die extrusion, the mechanical properties, surface hardness and heat resistance of the thermoplastic resin composition are improved, and the thermoplastic resin composition has excellent non-whitening property. Based on these results, the present inventors conducted further studies to complete the present invention.

[0037] The thermoplastic resin composition of the present invention is described in detail below.

[0038] The thermoplastic resin composition of the present invention comprises: 25 wt % to 75 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer (A) containing an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm; 18 wt % to 47 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (B) having a weight average molecular weight of 70,000 g / mol to 150,000 g / mol; and 3 wt % to 28 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (C) having a weight average molecular weight greater than 150,000 g / mol and less than or equal to 250,000 g / mol, wherein the thermoplastic resin composition has an alkyl acrylate coverage value (X) calculated by the following equation 1 of 67% or more. In this case, the thermoplastic resin composition has excellent processability during calendering and T-die extrusion, excellent mechanical properties such as impact strength, tensile strength and elongation, surface hardness and heat resistance, and excellent non-whitening property.

[0039] [Equation 1]

[0040] X={(GY) / Y}×100

[0041] In Equation 1, G represents the gel content (wt%) based on the total weight of the thermoplastic resin composition, and Y represents the content (wt%) of the alkyl acrylate in the gel based on the total weight of the thermoplastic resin composition.

[0042] Hereinafter, each component constituting the thermoplastic resin composition of the present invention will be described in detail.

[0043] (A) Alkyl acrylate - Aromatic vinyl compounds - Vinyl cyanide graft copolymer

[0044] For example, the graft copolymer (A) may contain an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm, preferably 60 nm to 120 nm, more preferably 80 nm to 110 nm. Within this range, the finally prepared thermoplastic resin composition may have excellent impact strength and gloss.

[0045] In this specification, the average particle size can be measured by dynamic light scattering, specifically, it can be measured using a particle size analyzer (product name: Nicomp 380, manufacturer: PSS) in Gaussian mode as an intensity value. As a specific measurement example, a sample can be prepared by diluting 0.1g of latex (TSC: 35 to 50 wt%) by 1000 to 5000 times with distilled water, and the average particle size can be measured using a flow cell in an automatic dilution mode in a mode of dynamic light scattering / intensity 300kHz / intensity-weighted Gaussian analysis. At this time, the temperature can be set to 23°C, the measurement wavelength can be set to 632.8nm, and the channel width can be set to 10μsec.

[0046] For example, based on the total weight of components (A), (B) and (C), the content of the graft copolymer (A) may be 25 to 75 wt %, preferably 30 to 70 wt %, more preferably 40 to 60 wt %, and even more preferably 45 to 55 wt %. Within this range, excellent processability may be achieved during calendering and T-die extrusion, and mechanical properties such as impact strength, tensile strength and elongation, gloss and surface hardness may be excellent.

[0047] For example, the graft copolymer (A) may contain 20 to 60% by weight of the alkyl acrylate rubber (a-1) and 40 to 80% by weight of the aromatic vinyl compound-vinyl cyanide compound copolymer (a-2), preferably 30 to 50% by weight of the alkyl acrylate rubber (a-1) and 50 to 70% by weight of the aromatic vinyl compound-vinyl cyanide compound copolymer (a-2), more preferably 40 to 50% by weight of the alkyl acrylate rubber (a-1) and 50 to 60% by weight of the aromatic vinyl compound-vinyl cyanide compound copolymer (a-2). Within this range, mechanical properties, gloss and surface hardness may be excellent.

[0048] In the present specification, a polymer containing a certain compound refers to a polymer obtained by polymerizing the compound, and a unit in the polymer is derived from the compound.

[0049] For example, the alkyl acrylate rubber (a-1) may further include an aromatic vinyl compound. In this case, chemical resistance and impact resistance may be excellent. For example, based on a total of 100 wt % of acrylate rubber, the alkyl acrylate rubber (a-1) may include 0.1 wt % to 25 wt %, preferably 2 wt % to 23 wt %, more preferably 5 wt % to 20 wt %, more preferably 10 wt % to 20 wt % of an aromatic vinyl compound. Within this range, mechanical properties, gloss and surface hardness may be excellent without deterioration of physical properties.

[0050] For example, the copolymer (a-2) may further contain an alkyl acrylate. In this case, the physical property balance among impact resistance, weather resistance, processability, and non-whitening property may be excellent.

[0051] For example, based on 100 wt % of the copolymer (a-2) in total, the copolymer (a-2) may contain 55 wt % to 85 wt % of an aromatic vinyl compound, 10 wt % to 30 wt % of a vinyl cyanide compound, and 0.1 wt % to 20 wt % of an alkyl acrylate, preferably 60 wt % to 80 wt % of an aromatic vinyl compound, 13 wt % to 26 wt % of a vinyl cyanide compound, and 3 wt % to 20 wt % of an alkyl acrylate, and more preferably 65 wt % to 78 wt % of an aromatic vinyl compound, 15 wt % to 22 wt % of a vinyl cyanide compound, and 5 wt % to 17 wt % of an alkyl acrylate. Within this range, impact resistance and weather resistance may be excellent.

[0052] For example, the graft copolymer (A) may be prepared by emulsion polymerization. In this case, gloss and surface hardness may be excellent.

[0053] For example, the alkyl acrylate may be an alkyl acrylate containing an alkyl group having 1 to 15 carbon atoms, preferably including one or more selected from the group consisting of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylbutyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, hexyl acrylate, heptyl acrylate, n-pentyl acrylate, and lauryl acrylate. More preferably, the alkyl acrylate is an alkyl acrylate having 2 to 8 carbon atoms, still more preferably butyl acrylate, ethylhexyl acrylate, or a mixture thereof, still more preferably butyl acrylate.

[0054] For example, the aromatic vinyl compound may include one or more selected from the group consisting of styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, m-methylstyrene, ethylstyrene, isobutylstyrene, tert-butylstyrene, o-bromostyrene, p-bromostyrene, m-bromostyrene, o-chlorostyrene, p-chlorostyrene, m-chlorostyrene, vinyltoluene, vinylxylene, fluorostyrene and vinylnaphthalene, preferably one or more selected from the group consisting of styrene and α-methylstyrene, more preferably styrene. In this case, due to appropriate fluidity, processability may be excellent, and mechanical properties such as impact resistance may be excellent.

[0055] For example, the vinyl cyanide compound may include one or more selected from the group consisting of acrylonitrile, methacrylonitrile, ethacrylonitrile and isopropylacrylonitrile, preferably acrylonitrile.

[0056] Emulsion polymerization generally practiced in the art to which the present invention pertains can be used in the present invention without particular limitation.

[0057] For example, the graft copolymer (A) may have a grafting degree calculated by the following equation 3 of 60% or more, preferably 60% to 150%, more preferably 62% to 140%, still more preferably 65% ​​to 130%, still more preferably 65% ​​to 100%, still more preferably 65% ​​to 80%. Within this range, impact resistance, processability and non-whitening property may be excellent.

[0058] [Equation 3]

[0059] Grafting degree (%) = [grafting monomer weight (g) / rubber weight (g)] × 100

[0060] In Equation 3, the graft monomer weight (g) is obtained by subtracting the rubber weight (g) from the weight of the insoluble matter (gel) obtained by dissolving the graft copolymer in acetone and centrifuging it, and the rubber weight (g) is the weight (g) of the rubber component theoretically added to the graft copolymer powder.

[0061] When measuring the insoluble matter (gel) weight, 0.5 g of powdered graft copolymer (A) was added to 50 ml of acetone and then stirred at room temperature for 12 hours. Then, centrifugation was performed to separate the insoluble matter that was insoluble in acetone and then dried for 12 hours. Then, the insoluble matter (gel) weight was measured. The rubber weight (g) is the weight (g) of the rubber component theoretically added to 0.5 g of powdered graft copolymer (A).

[0062] As a specific measurement example, when measuring the weight (g) of insoluble matter (gel), 0.5g of powdered graft copolymer was added to 50ml of acetone, and then stirred at 210rpm for 12 hours at room temperature using an orbital oscillator (device name: Lab companion SKC-6075). Then, centrifuge (Supra R30, Hanil Scienece) was used to centrifuge for 3 hours at 0°C and 18000rpm to separate the insoluble matter insoluble in acetone, and then dried for 12 hours by forced circulation in a forced convection oven (device name: Lab companion OF-12GW) set at 85°C. Then, the weight of insoluble matter (gel) was measured.

[0063] (B) weight average molecular weight is 70000 g / mol to 1 50000g / mol of aromatic vinyl compounds - Vinyl cyanide Copolymer

[0064] The weight average molecular weight of copolymer (B) is preferably 80000 g / mol to 130000 g / mol, more preferably 80000 g / mol to 110000 g / mol, and even more preferably 85000 g / mol to 100000 g / mol. Within this range, excellent processability can be achieved during calendering and T-die extrusion, and mechanical properties such as impact strength, tensile strength and elongation, gloss and surface hardness can be excellent.

[0065] In this specification, unless otherwise defined, weight average molecular weight can be measured using gel permeation chromatography (GPC, Waters Breeze). As a specific example, weight average molecular weight can be measured by gel permeation chromatography (GPC, Waters Breeze) using tetrahydrofuran (THF) as eluent. In this case, weight average molecular weight is obtained as a relative value relative to a polystyrene (PS) standard sample. As a specific measurement example, the weight-average molecular weight can be measured under the following conditions: solvent: tetrahydrofuran, column temperature: 40°C, flow rate: 0.3 ml / min, sample concentration: 20 mg / ml, injection volume: 5 μl, column model: 1×PLgel10μm MiniMix-B (250×4.6 mm) + 1×PLgel 10μm MiniMix-B (250×4.6 mm) + 1×PLgel 10μmMiniMix-B Guard (50×4.6 mm), equipment name: Agilent 1200 series system, refractive index detector: Agilent G1362 RID, RI temperature: 35°C, data processing: Agilent ChemStation S / W, test method (Mn, Mw and PDI): OECD TG 118.

[0066] For example, based on the total weight of components (A), (B) and (C), the content of copolymer (B) may be 18 to 47% by weight, preferably 25 to 45% by weight, more preferably 30 to 40% by weight, and even more preferably 33 to 37% by weight. Within this range, excellent processability can be achieved during calendering and T-die extrusion, and mechanical properties such as impact strength, tensile strength and elongation, gloss, surface hardness and non-whitening property can be excellent.

[0067] For example, copolymer (B) may contain 55 to 85% by weight of an aromatic vinyl compound and 15 to 45% by weight of a vinyl cyanide compound, preferably 60 to 80% by weight of an aromatic vinyl compound and 20 to 40% by weight of a vinyl cyanide compound, more preferably 65 to 75% by weight of an aromatic vinyl compound and 25 to 35% by weight of a vinyl cyanide compound. Within this range, excellent processability can be achieved during calendering and T-die extrusion, and gloss, surface hardness and non-whitening properties can be excellent.

[0068] For example, the aromatic vinyl compound may include one or more selected from the group consisting of styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, m-methylstyrene, ethylstyrene, isobutylstyrene, tert-butylstyrene, o-bromostyrene, p-bromostyrene, m-bromostyrene, o-chlorostyrene, p-chlorostyrene, m-chlorostyrene, vinyltoluene, vinylxylene, fluorostyrene and vinylnaphthalene, preferably styrene.

[0069] For example, the vinyl cyanide compound may include one or more selected from the group consisting of acrylonitrile, methacrylonitrile, ethacrylonitrile and isopropylacrylonitrile, preferably acrylonitrile.

[0070] The copolymer (B) is preferably a styrene-acrylonitrile copolymer (SAN resin), an α-methylstyrene-acrylonitrile copolymer (heat-resistant SAN resin) or a mixture thereof, and more preferably a styrene-acrylonitrile copolymer (SAN resin). In this case, excellent processability can be achieved during calendering and T-die extrusion, and gloss and surface hardness can be excellent.

[0071] For example, the copolymer (B) can be prepared by suspension polymerization, emulsion polymerization, solution polymerization or bulk polymerization, preferably bulk polymerization. In this case, mechanical properties can be excellent.

[0072] Suspension polymerization, emulsion polymerization, solution polymerization and bulk polymerization generally practiced in the art to which the present invention pertains can be used in the present invention without particular limitation.

[0073] (C) Aromatic vinyl compounds having a weight average molecular weight greater than 150,000 g / mol and less than or equal to 250,000 g / mol Polyvinyl cyanide copolymer

[0074] The weight average molecular weight of copolymer (C) is preferably 160000g / mol to 230000g / mol, more preferably 160000g / mol to 210000g / mol, and more preferably 160000g / mol to 190000g / mol. Within this range, excellent processability can be achieved during calendering and T-die extrusion, and gloss, surface hardness and non-whitening property can be excellent.

[0075] For example, based on the total weight of components (A), (B) and (C), the content of copolymer (C) may be 3% to 28% by weight, preferably 5% to 25% by weight, more preferably 10% to 25% by weight, and even more preferably 12% to 20% by weight. Within this range, excellent processability can be achieved during calendering and T-die extrusion, and gloss, surface hardness and non-whitening property can be excellent.

[0076] For example, copolymer (C) may contain 55% to 85% by weight of an aromatic vinyl compound and 15% to 45% by weight of a vinyl cyanide compound, preferably 60% to 80% by weight of an aromatic vinyl compound and 20% to 40% by weight of a vinyl cyanide compound, more preferably 65% ​​to 75% by weight of an aromatic vinyl compound and 25% to 35% by weight of a vinyl cyanide compound. Within this range, excellent processability can be achieved during calendering and T-die extrusion, and gloss, surface hardness and non-whitening properties can be excellent.

[0077] The copolymer (C) is preferably a styrene-acrylonitrile copolymer (SAN resin). In this case, excellent processability can be achieved during calendaring and T-die extrusion, and gloss and surface hardness can be excellent.

[0078] For example, the copolymer (C) can be prepared by suspension polymerization, emulsion polymerization, solution polymerization or bulk polymerization, preferably bulk polymerization. In this case, mechanical properties can be excellent.

[0079] Suspension polymerization, emulsion polymerization, solution polymerization and bulk polymerization generally practiced in the art to which the present invention pertains can be used in the present invention without particular limitation.

[0080] For example, the content of copolymer (C) may be less than that of copolymer (B). Preferably, the weight ratio (B:C) of copolymer (B) to copolymer (C) is 1.5:1 to 5.5:1, more preferably 1.7:1 to 5:1, even more preferably 2:1 to 4:1, even more preferably 2:1 to 3:1. Within this range, processability during calendering and T-die extrusion may be excellent, and non-whitening property may be excellent.

[0081] Thermoplastic resin composition

[0082] The thermoplastic resin composition of the present invention preferably has an alkyl acrylate coverage value (X) calculated by the following equation 1 of 67% or more, preferably 67% to 150%, more preferably 70% to 140%, even more preferably 75% to 120%, even more preferably 75% to 110%. Within this range, mechanical properties such as impact strength, tensile strength and elongation, surface hardness and heat resistance can be excellent. In particular, due to excellent non-whitening property, whitening during bending can be prevented.

[0083] [Equation 1]

[0084] X={(GY) / Y}×100

[0085] In Equation 1, G represents the gel content (wt%) based on the total weight of the thermoplastic resin composition, and Y represents the content (wt%) of the alkyl acrylate in the gel based on the total weight of the thermoplastic resin composition.

[0086] In Equation 1, the content of alkyl acrylate in the gel of the thermoplastic resin composition is the content of alkyl acrylate in the insoluble matter obtained in the process of measuring the above-mentioned gel content (based on 100% by weight of the added thermoplastic resin composition in total). Here, the gel content is based on the insoluble matter content of the thermoplastic resin composition in total 100% by weight.

[0087] The content of alkyl acrylate in the gel can be quantitatively measured by nuclear magnetic resonance (NMR) analysis or Fourier transform infrared spectroscopy (FT-IR) analysis.

[0088] In this specification, unless otherwise specified, NMR analysis refers to 1 Analysis by H NMR.

[0089] In this specification, NMR analysis commonly performed in the art can be used in the present invention, and specific measurement examples are as follows.

[0090] - Equipment name: Bruker 600MHz NMR (AVANCE III HD) CPP BB (1H 19F tunable and broadband, with z gradient) Prodigy Probe

[0091] -Measurement conditions: 1 H NMR (zg30): ns=32, d1=5s, TCE-d2, room temperature

[0092] When measuring the gel content, 1g of the thermoplastic resin composition was added to 30ml of acetone and then stirred at room temperature for 12 hours. Then, centrifugation was performed to separate the insoluble matter insoluble in acetone, followed by drying for 12 hours. Then, the gel content was measured and calculated by the following equation 2. As a specific measurement example, when measuring the gel content, 1g of the thermoplastic resin composition was added to 30ml of acetone, and then an orbital oscillator (device name: Lab companion SKC-6075) was used to stir at room temperature at 210rpm for 12 hours. Then, a centrifuge (Supra R30, Hanil Scienece Company) was used to centrifuge at 0°C and 18000rpm for 3 hours to separate the insoluble matter insoluble in acetone, and then dried for 12 hours by forced circulation in a forced convection oven (device name: Lab companion OF-12GW) set at 85°C. Then, the gel content was measured.

[0093] [Equation 2]

[0094] Gel content (weight %) = [weight of insoluble matter (gel) (g) / sample weight (g)] × 100

[0095] In this specification, the alkyl acrylate coverage value is a parameter for measuring the dispersion degree of the aromatic vinyl compound-vinyl cyanide compound polymer grafted on the alkyl acrylate rubber in the thermoplastic resin composition. When the alkyl acrylate coverage value is high, the aromatic vinyl compound-vinyl cyanide compound polymer is uniformly grafted to the alkyl acrylate rubber to uniformly cover the alkyl acrylate rubber, thereby increasing the gloss and achieving excellent tensile strength, colorability and non-whitening properties. In addition, as the alkyl acrylate coverage value increases, the distance between rubber particles decreases, thereby reducing the voids due to cracks generated inside the thermoplastic resin composition and suppressing whitening during bending.

[0096] Here, the alkyl acrylate coverage value indicates the degree of dispersion of the aromatic vinyl compound-vinyl cyanide compound polymer grafted onto the alkyl acrylate in the thermoplastic resin composition, and the grafting degree indicates the degree to which the aromatic vinyl compound-vinyl cyanide compound polymer is grafted onto the alkyl acrylate in the alkyl acrylate-aromatic vinyl compound-vinyl cyanide graft copolymer.

[0097] In addition, the alkyl acrylate coverage value is obtained by quantitatively calculating the content of alkyl acrylate present in the thermoplastic resin composition by nuclear magnetic resonance (NMR) analysis or Fourier transform infrared spectroscopy (FT-IR) analysis, and the grafting degree is obtained based on the content of the rubber component added during polymerization.

[0098] For example, the thermoplastic resin composition may have a melt index (220° C., 10 kg) measured according to ASTM D1238 of 1.8 to 21 g / 10 min, preferably 2 to 20.5 g / 10 min, more preferably 4 to 20.5 g / 10 min, even more preferably 9 to 20.5 g / 10 min, even more preferably 15 to 20.5 g / 10 min. Within this range, excellent processability may be achieved during calendaring and T-die extrusion, and non-whitening property may be excellent.

[0099] Since the thermoplastic resin composition of the present invention has physical properties suitable for calendering, the thermoplastic resin composition is preferably a thermoplastic resin composition for calendering.

[0100] Furthermore, since the thermoplastic resin composition of the present invention has physical properties suitable for T-die extrusion processing, the thermoplastic resin composition is preferably a thermoplastic resin composition for T-die extrusion processing.

[0101] For example, the thermoplastic resin composition may have an Izod impact strength (specimen thickness: 1 / 4", room temperature) measured according to ASTM D256 of 3 kgf·cm / cm or more, preferably 3 kgf·cm / cm to 10 kgf·cm / cm. Within this range, the balance of physical properties may be excellent, and the processability during calendering and T-die extrusion may be excellent.

[0102] In this specification, the room temperature may be a temperature within 20±5°C.

[0103] For example, when a 1 kg weight is dropped vertically from a height of 25 cm onto an extruded film having a size of 0.15 mm×10 cm×10 cm in thickness, width, and length using a Gardner impact tester, and the haze values ​​before and after the impact are measured for the portion of the film impacted by the weight and the haze value difference is calculated according to ASTM D1003, the thermoplastic resin composition may have a haze difference (Δhaze) of 5.5 or less, preferably 5 or less, more preferably 4.5 or less, still more preferably 4 or less, and still more preferably 1 to 4. In this case, since the thermoplastic resin has excellent non-whitening property with respect to external impact (impact), the thermoplastic resin may have an excellent appearance.

[0104] For example, when a sheet having a thickness of 0.15 mm is manufactured using a T-die extruder, the sheet is cut into a length of 100 cm, the thickness is measured at 10 or more locations except for an area 2 to 3 cm from both ends of the sheet, and the thickness deviation is calculated based on the difference between the maximum and minimum thicknesses, the thickness deviation of the thermoplastic resin composition may be 0.06 mm or less, preferably 0.05 mm or less, and more preferably 0.01 mm to 0.05 mm. In this case, the physical property balance and the non-whitening property may be excellent, and the extrusion moldability may be excellent.

[0105] In this specification, the thickness can be measured using ABSOLUTE ID-C1012BS (Mitutoyo Corporation).

[0106] As a specific example of using a T-die extruder to perform extrusion to obtain a sheet, extrusion can be performed using a T-die extruder (ST32HS (twin screw, 32Τ, L / D=44), Hankook EM Company) at an extrusion screw speed of 150 rpm to 200 rpm, an extrusion temperature of 200°C to 300°C, a 3-axis roller temperature of 80°C to 90°C, and a roller speed of 1 m / min to 5 m / min to obtain a sheet with a thickness of 0.15 mm.

[0107] For example, when the thermoplastic resin composition is extruded using a T-die extruder at an extrusion screw speed of 150 to 200 rpm, an extrusion temperature of 200 to 300° C., a 3-axis roll temperature of 80 to 90° C., and a roll speed of 2 to 4 m / min, a sheet of 80 cm or more can be obtained without tearing the sheet. In this case, the physical property balance and the non-whitening property can be excellent, and excellent extrusion processability can be ensured even at a high roll speed.

[0108] As a specific example, ST32HS (twin screw, 32Τ, L / D=44) manufactured by Hankook EM Corporation can be used as the T-die extruder.

[0109] For example, when a sheet having a length and width of 15 cm×15 cm is manufactured by calendaring using a roll mill, the thickness is measured at 10 or more locations except for an area 2 to 3 cm from both ends of the sheet, and the thickness deviation is calculated based on the difference between the maximum and minimum thicknesses, the thickness deviation of the thermoplastic resin composition may be 0.09 mm or less, preferably 0.08 mm or less, more preferably 0.07 mm or less, and even more preferably 0.01 mm to 0.07 mm. Within this range, the sheet quality and physical property balance may be excellent, and the processability during calendaring may be excellent.

[0110] For example, calendering can be performed using a rolling mill (MR-LM0820, Mirae RPM Co.) at a roll-to-roll distance of 0.3 mm at a temperature of two calendering rolls of 180 to 220° C. and a calendering roll speed of 8 to 12 rpm.

[0111] For example, the thermoplastic resin composition may have heat resistance measured under a load of 18.6 kgf according to ASTM D648 of 71° C. or more, preferably 73° C. or more, more preferably 75° C. or more, still more preferably 80° C. or more, still more preferably 80° C. to 85° C. In this case, the balance of all physical properties may be excellent.

[0112] For example, the thermoplastic resin composition may have a gloss measured at an incident angle of 45° according to ASTM D2457 of 95 or more, preferably 97 or more, more preferably 97 to 105. Within this range, physical property balance may be excellent, and processability during calendaring and T-die extrusion may be excellent.

[0113] For example, the thermoplastic resin composition may have a tensile strength of 300 kgf / cm2 measured according to ASTM D638 using a sample having a thickness of 3.2 mm at a crosshead speed of 50 mm / min. 2 Above, preferably 350kgf / cm 2 More preferably 400kgf / cm2 More preferably, 500 kgf / cm 2 More preferably, 500 kgf / cm 2 Up to 600kgf / cm 2 Within this range, the balance of physical properties can be excellent, and processability during calendering and T-die extrusion can be excellent.

[0114] For example, the thermoplastic resin composition may have an elongation of 40% or more, preferably 45% or more, and more preferably 45% to 70% measured at a crosshead speed of 50 mm / min using a sample having a thickness of 3.2 mm according to ASTM D638. Within this range, excellent processability may be achieved during calendering and T-die extrusion, and a balance of physical properties may be excellent.

[0115] For example, the thermoplastic resin composition may have a Rockwell hardness measured by R scale according to ASTM D785 of 70 or more, preferably 80 or more, more preferably 90 or more, and still more preferably 95 to 110. Within this range, the physical property balance may be excellent, the generation of indentation may be prevented, and thus the appearance may be excellent.

[0116] If necessary, the thermoplastic resin composition may further contain one or more selected from the group consisting of a heat stabilizer, a light stabilizer, a dye, a pigment, a colorant, a lubricant, a mold release agent, an antistatic agent, an antibacterial agent, a processing aid, a metal deactivator, a flame retardant, a smoke suppressant, an anti-drip agent, a friction reducing agent, and an anti-wear agent, based on 100 parts by weight of the total of the components (A), (B), and (C). Within this range, the desired physical properties of the thermoplastic resin composition of the present invention can be achieved without deteriorating its inherent physical properties.

[0117] The heat stabilizer preferably includes a primary heat stabilizer and a secondary heat stabilizer.

[0118] For example, the primary heat stabilizer may be a phenolic heat stabilizer, preferably selected from 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 1,6-hexanediol di[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2-thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid diethyl ester, tris(2,6-dimethyl-3-hydroxy-4-tert-butylbenzyl) isocyanurate, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, tris[(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxyethyl] isocyanurate, One or more of the group consisting of tris(4-tert-butyl-2,6-dimethyl-3-hydroxybenzyl)isocyanurate, 2,2'-methylenebis(4-methyl-6-tert-butylphenol)terephthalate, 1,3,5-trimethyl-2,4,6-(tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 3,9-bis[1,1-dimethyl-2-{β-(3-tert-butyl-4-hydroxy-5-methyl-phenyl)propionyloxy}ethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane, 2,2-bis[4-(2-3,5-di-tert-butyl-4-hydroxyhydrocinnamoyloxy)ethoxyphenyl]propane and stearyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, more preferably octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (IR1076).

[0119] For example, the secondary thermal stabilizer can be a phosphorus thermal stabilizer, preferably including a group selected from bis(dialkylphenyl)pentaerythritol diphosphite, phosphite, trioctyl phosphite, trilauryl phosphite, tridecyl phosphite, (octyl)diphenyl phosphite, tris(2,4-di-tert-butylphenyl) phosphite, triphenyl phosphite, tris(butoxyethyl) phosphite, tris(nonylphenyl) phosphite, distearylpentaerythritol diphosphite, tetra(tridecyl)-1,1,3-tridecyl (2-methyl)-5-tert-butyl-4-hydroxy-phenyl) butane diphosphite, tetra(C12-C15 mixed alkyl)-4,4'-isopropylidene diphenyl diphosphite, tetra(tridecyl)-4,4'-butylene bis(3-methyl-6-tert-butylphenol) diphosphite, tris(mixed monononylphenyl and dinonylphenyl) phosphite, hydrogenated 4,4'-isopropylidene diphenol polyphosphite, phenyl(4,4'-isopropylidene diphenol) pentaerythritol diphosphite Ester, distearyl pentaerythritol diphosphite, tris[4,4'-isopropylidene bis(2-tert-butylphenol)]phosphite, di(isodecyl)phenyl phosphite, 4,4'-isopropylidene di(2-tert-butylphenol)di(nonylphenyl)phosphite, di(2,4-di-tert-butyl-6-methylphenyl)ethylphosphite, 2-[{2,4,8,10-tetra-tert-butyldibenzo[d,f][1.3.2]-dioxaphosphocycloheptan-6-yl}oxy]-N,N -One or more of the group consisting of di[2-[{2,4,8,10-tetra-tert-butyl-dibenzo[d,f][1.3.2]-dioxaphosphopane-6-yl}oxy]ethyl]-ethylamine and 6-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenzo[d,f][1.3.2]-dioxaphosphopane, more preferably tris(2,4-di-tert-butylphenyl) phosphite (IF168).

[0120] The lubricant preferably includes one or more selected from the group consisting of aliphatic amide-based lubricants, fatty acid ester-based lubricants, and olefin-based waxes.

[0121] The aliphatic amide-based lubricant preferably comprises one or more selected from the group consisting of stearamide, oleamide, erucamide, ethylenebisstearamide, and ethylenebisoleamide.

[0122] The fatty acid ester lubricant preferably contains one or more selected from the group consisting of fatty acid esters of alcohols or polyols, hardened oils, butyl stearate, stearic acid monoglyceride, pentaerythritol tetrastearate, stearyl stearate, ester waxes, and alkyl phosphates.

[0123] The olefin wax is preferably polyethylene wax.

[0124] For example, the light stabilizer may include one or more selected from the group consisting of a HALS-type UV stabilizer and a benzotriazole-type UV stabilizer, preferably a mixture of a HALS-type UV stabilizer and a benzotriazole-type UV stabilizer.

[0125] The HALS UV stabilizer preferably includes one or more selected from the group consisting of di(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (UV770), di[N-methyl-2,2,6,6-tetramethyl-4-piperidinyl] sebacate and dimethyl-1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine succinate (Tinuvin 622), more preferably di(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (UV 770).

[0126] The benzotriazole UV stabilizer preferably includes 2-(2'-hydroxy-5'-tert-octylphenyl)-benzotriazole (Cyasorb UV-541), 2-(2'-hydroxy-5'-methylphenyl)benzotriazole (Tinuvin-P), 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chloro-benzotriazole (Tinuvin-326), 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole (Tinuvin-327), 2-(2'-hydroxy-3,5-di-tert-pentylphenyl)-5-chlorobenzotriazole (Tinuvin-328), 2-(2'-hydroxy-3,5-di-tert-pentylphenyl)-5-chlorobenzotriazole (Tinuvin-329), 2-(2'-hydroxy-3,5-di-tert-pentylphenyl)-5-chlorobenzotriazole (Tinuvin-321), 2-(2'-hydroxy-3,5-di-tert-pentylphenyl)-5-chlorobenzotriazole (Tinuvin-323). One or more of the group consisting of 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (UV 329), more preferably 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (UV 329).

[0127] Method for preparing thermoplastic resin composition

[0128] The preparation method of the thermoplastic resin composition of the present invention comprises the steps of mixing and extruding 25 wt % to 75 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer (A) containing an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm, 18 wt % to 47 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (B) having a weight average molecular weight of 70000 g / mol to 150000 g / mol, and 3 wt % to 28 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (C) having a weight average molecular weight of greater than 150000 g / mol and less than or equal to 250000 g / mol at 200° C. to 300° C. and 100 rpm to 500 rpm, wherein the thermoplastic resin composition has an alkyl acrylate coverage value (X) calculated by the following equation 1 of 67% or more. In this case, processability during calendering and T-die extrusion can be excellent, and mechanical properties, surface hardness, heat resistance, and non-whitening can be excellent.

[0129] [Equation 1]

[0130] X={(GY) / Y}×100

[0131] In Equation 1, G represents the gel content (wt%) based on the total weight of the thermoplastic resin composition, and Y represents the content (wt%) of the alkyl acrylate in the gel based on the total weight of the thermoplastic resin composition.

[0132] The method for preparing the thermoplastic resin composition has all the technical features of the above-mentioned thermoplastic resin composition, and thus repeated description thereof will be omitted.

[0133] The kneading and extrusion steps are preferably performed using an extrusion kneader at 200° C. to 300° C. at a size of 10pi to 199pi, more preferably at 210° C. to 260° C. at a size of 20pi to 80pi, and even more preferably at 220° C. to 250° C. at a size of 25pi to 75pi. Within this range, extrusion can be performed stably and kneading can be performed efficiently. At this time, the temperature is the barrel temperature, and pi represents the outer diameter of the screw (unit: mm).

[0134] An extruder and kneader commonly used in the field to which the present invention belongs may be used without particular limitation, and a twin-screw extruder and kneader is preferably used.

[0135] Molded products

[0136] The molded product of the present invention comprises the thermoplastic resin composition. In this case, the processability during calendering and T-die extrusion can be excellent, and the mechanical properties, surface hardness, heat resistance and non-whitening property can be excellent. Therefore, a molded product with an attractive appearance can be manufactured, and the thermoplastic resin composition can be applied to manufacture a film or sheet product.

[0137] The molded product is preferably an injection molded product, a calender molded product or a T-die extrusion molded product. In this case, in addition to mechanical properties such as impact strength, tensile strength and elongation, glossiness and surface hardness, non-whitening property may also be excellent.

[0138] The molded article is preferably a film or a sheet, and specific examples thereof include decorative sheets for indoor furniture, interior decorations, etc., decorative materials for outdoor building materials, and decorative materials for roofs.

[0139] The method for producing a molded article preferably includes the steps of kneading and extruding 25 wt % to 75 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer (A) containing an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm, 18 wt % to 47 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (B) having a weight average molecular weight of 70,000 g / mol to 150,000 g / mol, and 3 wt % to 28 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (C) having a weight average molecular weight greater than 150,000 g / mol and less than or equal to 250,000 g / mol at 200° C. to 300° C. and 100 rpm to 500 rpm to obtain an extrudate, and injection molding, calendar molding or T-die extrusion molding the extrudate at a molding temperature of 180° C. to 300° C. to produce a molded article. In this case, processability and heat resistance may be excellent, and mechanical properties such as impact strength, tensile strength, and elongation, gloss, surface hardness, and non-whitening property may be excellent.

[0140] For example, the extrudate may be in the form of pellets or in the form of sheets.

[0141] In this specification, when a plate-like shape is generally defined as a plate-like shape in the technical field to which the present invention pertains, the plate-like shape is not particularly limited and may include, for example, a flat shape, a sheet shape, a film shape, and the like.

[0142] As a preferred example, the step of manufacturing a molded article may include the step of calendering the prepared extrudate at a calendering temperature of 140° C. to 220° C. to obtain a sheet. In this case, processability may be excellent, and a sheet having a uniform surface may be easily manufactured.

[0143] In this specification, calendaring is a process of calendaring an extrudate using a calendaring device including a calendaring roller. Without particular limitation, calendaring can be performed according to a method commonly used in the field to which the present invention belongs. Preferably, calendaring can be performed according to a method comprising the following steps: a step of mixing a thermoplastic resin composition pellet as a sheet raw material at 130°C to 220°C using a mixer, a step of manufacturing a substrate at 170°C to 240°C using the mixed raw material, and a step of manufacturing a sheet at 140°C to 220°C using a substrate and a calendaring roller. For example, a mixing roller can be used to perform the step of manufacturing a substrate.

[0144] As another preferred example, the method for manufacturing a molded article may include the step of injection molding the prepared extrudate at an injection temperature of 200° C. to 260° C., an injection pressure of 60 bar to 100 bar, and a holding pressure of 25 bar to 55 bar. In this case, an injection molded article having excellent mechanical properties such as impact strength can be easily manufactured.

[0145] The injection temperature is preferably 200° C. to 250° C., more preferably 210° C. to 240° C. Within this range, an injection-molded article having excellent mechanical properties such as impact strength can be easily produced.

[0146] The injection pressure is preferably 70 bar to 90 bar, more preferably 75 bar to 85 bar. Within this range, an injection molded product having excellent mechanical properties such as impact strength can be easily produced.

[0147] The holding pressure is preferably 30 bar to 50 bar, more preferably 35 bar to 50 bar. Within this range, an injection molded product having excellent mechanical properties such as impact strength can be easily produced.

[0148] As another preferred example, the method for manufacturing a molded article may include subjecting the prepared extrudate to T-die extrusion molding at an extrusion temperature of 200° C. to 300° C., an extrusion screw speed of 50 rpm to 200 rpm, a 3-axis roller temperature of 60° C. to 100° C., and a roller rotation speed of 1 m / min to 5 m / min. In this case, processability can be excellent, and a sheet having a uniform surface can be easily manufactured.

[0149] When describing the thermoplastic resin composition, the method for preparing the thermoplastic resin composition, and the molded article comprising the thermoplastic resin composition of the present invention, it should be noted that other conditions or equipment not explicitly described herein may be appropriately selected within the scope generally practiced in the art without particular limitation.

[0150] Hereinafter, the present invention will be described in more detail with reference to the following preferred embodiments. However, these embodiments are provided for illustrative purposes only and should not be construed as limiting the scope and spirit of the present invention. In addition, it will be apparent to those skilled in the art that various changes and modifications may be made without departing from the scope and spirit of the present invention, and such changes and modifications are also within the scope of the appended claims.

[0151] Example

[0152] The materials used in the following Examples and Comparative Examples are as follows.

[0153] Graft copolymer (A-1): ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 90 nm to 110 nm prepared by emulsion polymerization (core: 38 wt% butyl acrylate and 7 wt% styrene, shell: 4 wt% butyl acrylate, 40 wt% styrene and 11 wt% acrylonitrile, grafting degree: 70%)

[0154] Graft copolymer (A-2): ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 90 nm to 110 nm prepared by emulsion polymerization (core: 37 wt% butyl acrylate and 9 wt% styrene, shell: 4 wt% butyl acrylate, 39 wt% styrene and 11 wt% acrylonitrile, grafting degree: 70%)

[0155] Graft copolymer (A-3): ASA graft copolymer containing alkyl acrylate rubber having an average particle size of 90 nm to 110 nm prepared by emulsion polymerization (core: 38 wt% butyl acrylate and 2 wt% styrene, shell: 4 wt% butyl acrylate, 43 wt% styrene and 13 wt% acrylonitrile, grafting degree: 70%)

[0156] Graft copolymer (A-4): ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 90 nm to 110 nm prepared by emulsion polymerization (core: 38 wt% butyl acrylate and 7 wt% styrene, shell: 4 wt% butyl acrylate, 40 wt% styrene and 11 wt% acrylonitrile, grafting degree: 60%)

[0157] Graft copolymer (A-5): ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 90 nm to 110 nm prepared by emulsion polymerization (core: 38 wt% butyl acrylate and 2 wt% styrene, shell: 8 wt% butyl acrylate, 41 wt% styrene and 11 wt% acrylonitrile, grafting degree: 70%)

[0158] Graft copolymer (A-6): ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 90 nm to 110 nm prepared by emulsion polymerization (core: 43 wt% butyl acrylate and 2 wt% styrene, shell: 4 wt% butyl acrylate, 40 wt% styrene and 11 wt% acrylonitrile, grafting degree: 50%)

[0159] Graft copolymer (A-7): ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 280 nm to 330 nm prepared by emulsion polymerization (core: 43 wt% butyl acrylate and 17 wt% styrene, shell: 4 wt% butyl acrylate, 26 wt% styrene and 10 wt% acrylonitrile, grafting degree: 40%)

[0160] Graft copolymer (A-8): ASA graft copolymer containing an alkyl acrylate rubber having an average particle size of 25 nm to 35 nm prepared by emulsion polymerization (core: 43 wt% butyl acrylate and 7 wt% styrene, shell: 4 wt% butyl acrylate, 35 wt% styrene and 11 wt% acrylonitrile, grafting degree: 80%)

[0161] Graft copolymer (A-9): ASA graft copolymer containing alkyl acrylate rubber having an average particle size of 180 nm to 220 nm prepared by emulsion polymerization (core: 43 wt% butyl acrylate and 7 wt% styrene, shell: 4 wt% butyl acrylate, 35 wt% styrene and 11 wt% acrylonitrile, grafting degree: 70%)

[0162] SAN resin (B) prepared by bulk polymerization: 95RF (weight average molecular weight: 90,000 g / mol, LG Chemical Co., Ltd.)

[0163] SAN resin (C) prepared by bulk polymerization: 97HC (weight average molecular weight: 170,000 g / mol, LG Chemical Co., Ltd.)

[0164] Examples 1 to 7 and Comparative Examples 1 to 8

[0165] According to the contents shown in Tables 1 and 2, the components shown in Tables 1 and 2 were put into a twin-screw extruder. At this time, 0.1 to 2 parts by weight of lubricant (PASFLOW7501, Patech Fine Chemical), primary heat stabilizer (IR1076), secondary heat stabilizer (IF168), HALS UV stabilizer (UV 770) and benzotriazole UV stabilizer (UV329) were put into a twin-screw extruder. Then, melt mixing and extrusion were carried out at 230°C and 150rpm to prepare pellets. The melt index and alkyl acrylate coverage value of the prepared pellets were measured. Then, the pellets were injection molded using an injection molding machine (VC 330 / 80TECJPRO, ENGEL) at 200°C to 240°C and a screw speed of 100rpm to 200rpm to obtain samples for appearance and physical property evaluation. In addition, a sheet having a thickness of 0.15 mm was prepared using the prepared pellets and a T-die extruder (ST32HS (twin screw, 32T, L / D=44), Hankook EM Co.) at an extrusion screw speed of 150 to 200 rpm, a temperature of 200 to 280° C., a 3-axis roller temperature of 80° C., and a roller rotation speed of 1.5 m / min. Then, the haze difference and whitening occurrence caused by falling balls were measured.

[0166] [Test example]

[0167] The properties of the pellets or samples prepared in Examples 1 to 7 and Comparative Examples 1 to 8 were measured according to the following methods, and the results are shown in Tables 1 and 2 and Figure 1 middle.

[0168] Measurement method

[0169] *Alkyl acrylate coverage value (%): The alkyl acrylate coverage value was calculated by the following Equation 1.

[0170] [Equation 1]

[0171] X={(GY) / Y}×100

[0172] In Equation 1, G represents the gel content (wt%) based on the total weight of the thermoplastic resin composition, and Y represents the content (wt%) of the alkyl acrylate in the gel based on the total weight of the thermoplastic resin composition.

[0173] Here, the content of alkyl acrylate in the gel is determined by 1 Quantitative measurement is performed by HNMR analysis or FT-IR analysis.

[0174] 1 H NMR

[0175] - Equipment name: Bruker 600MHz NMR (AVANCE III HD) CPP BB (1H 19F tunable and broadband, with z gradient) Prodigy Probe

[0176] -Measurement conditions: 1 H NMR (zg30): ns=32, d1=5s, TCE-d2, room temperature

[0177] FT-IR

[0178] -Device Name: Agilent Cary 660

[0179] -Measurement conditions: ATR mode

[0180] When measuring the gel content, 1 g of pellets obtained by extruding the thermoplastic resin composition was added to 30 ml of acetone, and then stirred at 210 rpm for 12 hours at room temperature using an orbital oscillator (device name: Lab companion SKC-6075). Then, centrifugation was performed at 0°C and 18000 rpm for 3 hours using a centrifuge (Supra R30, Hanil Scienece) to separate insoluble matter insoluble in acetone, and then dried for 12 hours by forced circulation in a forced convection oven (device name: Labcompanion OF-12GW) set at 85°C. Then, the gel content was measured and calculated by the following equation 2.

[0181] [Equation 2]

[0182] Gel content (weight %) = [weight of insoluble matter (gel) (g) / sample weight (g)] × 100

[0183] *Grafting degree (%): 0.5 g of the powdered graft copolymer was added to 50 ml of acetone, stirred at room temperature for 12 hours, and then centrifuged to separate the insoluble matter that was insoluble in acetone, and dried for 12 hours. The weight of the insoluble matter was measured, and the grafting degree was calculated by the following equation 3.

[0184] [Equation 3]

[0185] Grafting degree (%) = [grafting monomer weight (g) / rubber weight (g)] × 100

[0186] In Equation 3, the graft monomer weight (g) is obtained by subtracting the rubber weight (g) from the weight of the insoluble matter (gel) obtained by dissolving the graft copolymer in acetone and centrifuging it, and the rubber weight (g) is the weight (g) of the rubber component theoretically added to the graft copolymer powder.

[0187] Specifically, when measuring the weight (g) of insoluble matter (gel), 0.5 g of powdered graft copolymer was added to 50 ml of acetone, and then stirred at 210 rpm for 12 hours at room temperature using an orbital oscillator (device name: Lab companion SKC-6075). Then, centrifuge (Supra R30, Hanil Scienece) was used to separate the insoluble matter insoluble in acetone at 0 ° C and 18000 rpm for 3 hours, and then dried by forced circulation for 12 hours in a forced convection oven (device name: Labcompanion OF-12GW) set at 85 ° C. Then, the weight of insoluble matter (gel) was measured.

[0188] * Melt index (MI, g / 10 min): Melt index was measured at 220° C. under a load of 10 kg for 10 minutes according to ASTM D1238.

[0189] *Izod impact strength (IMP, kgf·cm / cm): The Izod impact strength was measured at 23° C. using an injection molded sample (thickness: 1 / 4”) according to ASTM D256.

[0190] *Gloss: Gloss was measured according to ASTM D2457 using an injection molded sample (thickness: 1 / 4") and a gloss meter at an incident angle of 45°.

[0191] *Tensile strength (kgf / cm 2 ): The tensile strength was measured according to ASTM D638 using an injection molded specimen (thickness: 3.2 mm) at a crosshead speed of 50 mm / min.

[0192] *Elongation (%): The elongation was measured at a crosshead speed of 50 mm / min using an injection molded specimen (thickness: 3.2 mm) according to ASTM D638.

[0193] *Surface hardness: Rockwell hardness was measured using an injection molded sample (thickness: 3.2 mm) with an R scale according to ASTM D785.

[0194] *Heat deformation temperature (HDT, °C): The heat deformation temperature was measured under a load of 18.6 kgf according to ASTM D648.

[0195] *Whether whitening occurs after ball drop: A 1 kg weight is dropped vertically from a height of 25 cm onto a T-die extruded film having a thickness, width, and length of 0.15 mm×10 cm×10 cm using a Gardner impact tester. Then, whether whitening occurs in the portion hit by the weight is determined by visual observation, and the occurrence of whitening is evaluated according to the following criteria.

[0196] X: No whitening occurs after the ball falls (no whitening)

[0197] ○: *Whitening occurs after the ball falls

[0198] *Difference in haze due to falling ball (△ haze): A 1 kg weight was dropped vertically from a height of 25 cm onto a T-die extruded film having a thickness, width, and length of 0.15 mm×10 cm×10 cm using a Gardner impact tester. Then, the haze value of the portion of the film hit by the weight before and after the impact was measured according to ASTM D1003, and the haze difference was calculated by the following equation 4.

[0199] [Equation 4]

[0200] Haze difference (△ haze) = haze value after ball drop - haze value before ball drop

[0201] * Calendering processability: The thermoplastic resin composition in the form of pellets was calendered using a rolling mill (MR-LM0820, Mirae RPM) equipped with two calendering rolls of 30 cm in diameter at an interval of 0.3 mm while maintaining the temperature of the calendering rolls at 180° C. to 210° C. to obtain a sheet having a thickness, length, and width of 0.3 mm×15 cm×15 cm. Then, the melting state of the resin, the degree of gas generation, and the degree of tearing when the sheet was attached to the calendering rolls were evaluated as follows, compared with PVC resin.

[0202] ◎: Better than PVC, ○: Equal to PVC, X: Inferior to PVC

[0203] *Thickness deviation after calendering (mm): Using a rolling mill (MR-LM0820, Mirae RPM) equipped with two calendering rolls of 30 cm in diameter at an interval of 0.3 mm, the extruded thermoplastic resin composition in the form of pellets was calendered while the temperature of the rolls was maintained at 180°C to 210°C to obtain a sheet with a thickness of 0.3 mm. Then, in the obtained sheet having a size of 15 cm (length) × 15 cm (width), the thickness was measured at 10 or more locations in an area other than an area within 2 to 3 cm from both ends, and the thickness deviation was calculated based on the difference between the maximum and minimum thicknesses. At this time, the thickness was measured using ABSOLUTE ID-C1012BS (Mitutoyo).

[0204] *T-die extrusion processability: In addition, using a T-die extruder (ST32HS (twin screw, 32T, L / D=44), Hankook E.M. Co.), T-die extrusion was performed at a screw speed of 150 to 200 rpm, a temperature of 200° C. to 280° C., a 3-axis roller temperature of 80° C., and a roller rotation speed of 1.5 m / min to obtain a sheet having a thickness of 0.15 mm. Then, using the obtained sheet, the melting state of the resin, the degree of gas generation, and the degree of tearing when the sheet was attached to a roller were evaluated as follows compared with PVC resin.

[0205] ◎: Better than PVC, ○: Equal to PVC, X: Inferior to PVC

[0206] *Thickness deviation after T-die extrusion (mm): In addition, using a T-die extruder (ST32HS (twin screw, 32T, L / D=44), Hankook EM Co.), T-die extrusion was performed at a screw speed of 150 rpm to 200 rpm, a temperature of 200°C to 280°C, a 3-axis roller temperature of 80°C, and a roller speed of 1.5 m / min to obtain a sheet with a thickness of 0.15 mm. The sheet was cut into a length of 100 cm, and the thickness of more than 10 positions was measured in the area of ​​the sheet except for the area within 2 to 3 cm from both ends, and the thickness deviation was calculated based on the difference between the maximum and minimum thicknesses. At this time, the thickness was measured using ABSOLUTE ID-C1012BS (Mitutoyo Co., Ltd.).

[0207] [Table 1]

[0208]

[0209] [Table 2]

[0210]

[0211] As shown in Tables 1 and 2, compared with Comparative Examples 1 to 8 outside the scope of the present invention, in the case of Examples 1 to 7 of the present invention, excellent processability is achieved during calendering and T-die extrusion, and gloss, surface hardness and heat resistance are excellent. In addition, mechanical properties such as impact strength, tensile strength and elongation are excellent. In addition, no whitening occurs after ball drop. On the contrary, in the case of Comparative Example 1 in which the content of the ASA graft copolymer (A) is lower than the scope of the present invention, the haze value changes significantly due to the impact caused by the ball drop, and the calendering processability deteriorates, resulting in whitening. In the case of Comparative Example 2 in which the content of the ASA graft copolymer (A) exceeds the scope of the present invention, the calendering processability and T-die extrusion processability are poor, and physical properties such as tensile strength and surface hardness deteriorate.

[0212] In the case of Comparative Examples 3 and 5, where the coverage ratio of alkyl acrylate was less than 67%, whitening occurred and the difference in haze was significant. In addition, the thickness variation after calendering and T-die processing was large.

[0213] In the case of Comparative Example 4 in which the content of the SAN resin (C) exceeded the range of the present invention, whitening occurred after ball dropping, and the haze value increased with the impact of the ball dropping.

[0214] In addition, in the case of Comparative Examples 6 to 8 containing ASA graft copolymers (A) of rubber having an average particle size outside the range of the present invention, the haze difference increases with the impact caused by the falling ball, and thus the whitening becomes more serious. In addition, the calendering processability and T-die extrusion processability are deteriorated.

[0215] as follows Figure 1 As shown, compared with Comparative Example 1, in Example 2 of the present invention, the occurrence of whitening after the ball falls is prevented.

Claims

1. A thermoplastic resin composition, comprising: 25 to 75 wt% of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer (A), wherein the graft copolymer (A) contains an alkyl acrylate rubber having an average particle size of 50 to 120 nm; 18 to 47 wt% of an aromatic vinyl compound-vinyl cyanide compound copolymer (B), wherein the weight average molecular weight of the copolymer (B) is 70,000 to 150,000 g / mol; and 3 to 28 wt% of an aromatic vinyl compound-vinyl cyanide compound copolymer (C), wherein the weight average molecular weight of the copolymer (C) is greater than 150,000 g / mol and less than or equal to 250,000 g / mol, in, The thermoplastic resin composition has an alkyl acrylate coverage value (X) of 67% or more calculated by the following equation 1: [Equation 1] X={(GY) / Y}×100%, wherein G represents the gel content in % by weight based on the total weight of the thermoplastic resin composition, Y represents the content of the alkyl acrylate in the gel in % by weight based on the total weight of the thermoplastic resin composition, wherein the graft copolymer (A) comprises 20 to 60 wt % of an alkyl acrylate rubber (a-1) and 40 to 80 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (a-2), and The alkyl acrylate rubber (a-1) contains an aromatic vinyl compound in an amount of 0.1 to 25 wt %.

2. The thermoplastic resin composition according to claim 1, wherein The graft copolymer (A) comprises 30 to 50 wt % of an alkyl acrylate rubber (a-1) and 50 to 70 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (a-2).

3. The thermoplastic resin composition according to claim 1, wherein The graft copolymer (A) has a grafting degree calculated by the following equation 3 of 60% or more: [Equation 3] Grafting degree = [grafting monomer weight in g / rubber weight in g] × 100%, The weight of the grafted monomer in g is obtained by subtracting the weight of the rubber in g from the weight of the insoluble matter obtained as a gel by dissolving the grafted copolymer in acetone and centrifuging it, and the weight of the rubber in g is the weight of the rubber component in g theoretically added to the grafted copolymer powder.

4. The thermoplastic resin composition according to claim 1, wherein The aromatic vinyl compound-vinyl cyanide compound copolymer (B) and the aromatic vinyl compound-vinyl cyanide compound copolymer (C) each independently contain 55 to 85 wt % of an aromatic vinyl compound and 15 to 45 wt % of a vinyl cyanide compound.

5. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition comprises one or more selected from the group consisting of heat stabilizers, light stabilizers, colorants, mold release agents, antistatic agents, antibacterial agents, processing aids, metal deactivators, flame retardants, smoke suppressants, anti-drip agents, friction reducers and anti-wear agents.

6. The thermoplastic resin composition according to claim 5, wherein The colorant is a dye or a pigment.

7. The thermoplastic resin composition according to claim 5, wherein The processing aid is a lubricant.

8. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition has a melt index of 1.8 to 21 g / 10 min, measured at 220° C. and a load of 10 kg according to ASTM D1238.

9. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition has an Izod impact strength of 3 kgf·cm / cm or more measured at room temperature with a specimen thickness of 1 / 4" according to ASTM D256.

10. The thermoplastic resin composition according to claim 1, wherein When a 1 kg weight is dropped vertically from a height of 25 cm onto an extruded film having a thickness, a width, and a length of 0.15 mm×10 cm×10 cm using a Gardner impact tester, and the haze values ​​before and after the impact are measured for the portion of the film impacted by the weight and the haze value difference is calculated according to ASTM D1003, the thermoplastic resin composition has a haze difference of 5.5 or less.

11. The thermoplastic resin composition according to claim 1, wherein When a sheet having a thickness of 0.15 mm is manufactured using a T-die extruder, the sheet is cut into a length of 100 cm, the thickness is measured at 10 or more locations in an area excluding an area 2 cm to 3 cm from both ends of the sheet, and the thickness deviation is calculated based on the difference between the maximum and minimum thicknesses, the thermoplastic resin composition has a thickness deviation of 0.06 mm or less.

12. The thermoplastic resin composition according to claim 1, wherein When a sheet having a size of 15 cm×15 cm in length and width is manufactured by calendaring using a roll mill, the thickness is measured at 10 or more locations in an area excluding an area 2 cm to 3 cm from both ends of the sheet, and the thickness deviation is calculated based on the difference between the maximum and minimum thicknesses, the thermoplastic resin composition has a thickness deviation of 0.09 mm or less.

13. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition has a heat deformation temperature of 71° C. or higher measured under a load of 18.6 kgf according to ASTM D648.

14. A method for preparing a thermoplastic resin composition, the method comprising: 25 wt % to 75 wt % of an alkyl acrylate-aromatic vinyl compound-vinyl cyanide compound graft copolymer (A), 18 wt % to 47 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (B), and 3 wt % to 28 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (C) are kneaded and extruded at 200° C. to 300° C. and 100 rpm to 500 rpm, wherein the graft copolymer (A) contains an alkyl acrylate rubber having an average particle size of 50 nm to 120 nm, the copolymer (B) has a weight average molecular weight of 70,000 g / mol to 150,000 g / mol, and the copolymer (C) has a weight average molecular weight of greater than 150,000 g / mol and less than or equal to 250,000 g / mol, Wherein, the alkyl acrylate coverage value (X) of the thermoplastic resin composition calculated by the following equation 1 is 67% or more: [Equation 1] X={(GY) / Y}×100%, wherein G represents the gel content in % by weight based on the total weight of the thermoplastic resin composition, Y represents the content of the alkyl acrylate in the gel in % by weight based on the total weight of the thermoplastic resin composition, wherein the graft copolymer (A) comprises 20 to 60 wt % of an alkyl acrylate rubber (a-1) and 40 to 80 wt % of an aromatic vinyl compound-vinyl cyanide compound copolymer (a-2), and The alkyl acrylate rubber (a-1) contains an aromatic vinyl compound in an amount of 0.1 to 25 wt %. 15 . A molded article comprising the thermoplastic resin composition according to claim 1 .

16. The molded article according to claim 15, wherein The molded product is an injection molded product, a calender molded product or an extrusion molded product.

Citation Information

Patent Citations

  • Production of porous preform for optical fiber

    JP1995033470A

  • A method for measuring fine dust concentration using a terminal having a camera and a light emitting unit, a method for sharing measured fine dust concentration information, and a server for the method

    KR1020210009291A

  • Acrylate-styrene-acrylonitrile resin composition having excellent thermochromic resistant property under high temperature

    KR1020130075812A